Changing Perceived Life Control: Intergenerational Insights from Lithuania - Savicka, Aida (Socialinė teorija, empirija, politika ir praktika, 2025)
A substantial body of research underscores that greater perceived control over one’s life not only enhances the individual quality of life but also, at an aggregate level, fosters economic efficiency, social inclusion, and civic participation. Perceived control also plays a crucial role in enhancing resilience during crises. At the individual level, it helps to develop more effective coping mechanisms and mitigate psychological distress, engage in more proactive problem-solving strategies and maintain better health outcomes. At the societal level, it strengthens community cohesion that enhances mutual support, collaborative problem-solving and more coordinated crisis responses. Thus, effective strategies to maintain or increase perceived control can significantly buffer against the adverse effects of crises. However, social preconditions for the formation of perceived control and its broader societal implications remain insufficiently explored. This study examines the dynamics of perceived control in Lithuanian society through the lens of generational replacement, by utilizing the data from the European Values Survey which has been conducted in the country for almost three decades. The findings reveal notable differences in this attitude across social generations. Yet, a multilevel Age-Period-Cohort (APC) analysis indicates that, while generational shifts contribute to an overall societal increase in perceived control, the primary driver is a profound cultural transformation that cuts across all generations.